COVID-19 lockdown impact on university libraries in India and their response / M Masoom Raza, Abdul Moid and Keshwar Jahan - Raza, M Masoom; Moid, Abdul; Jahan, Keshwar (Faculty of Information Management, 2022)
Universities, other educational institutions, and libraries are closed due to the COVID-19 pandemic. Libraries face difficulties due to COVID-19 outbreaks but ensure continuity of the teaching and learning process. This research aimed to investigate the effects on university libraries and their responses to the COVID-19 lockdown in India. The researchers have collected data using a structured closed and open-ended online questionnaire and collected data has been interpreted and depicted in figures. The study discussed: awareness of COVID-19, library status, communication channels, target users, resource availability and shareability, and how libraries fulfil user requirements and challenges. Overall, the study tried to find out the availability and accessibility of library services and contents during COVID-19 lockdown. The current study will be the basis for reconsidering education budgets, particularly for ICT infrastructure in India's central and state provinces.